Newsletter for Europe: No.44, April 2012 - Bioversity International (2012)
This is the last issue of the Newsletter for Europe. During its structural reorganization, Bioversity decided to close its Regional Office for Europe and integrate the European Cooperative Programme for Plant Genetic Resources (ECPGR) and for the European Forest Genetic Resources Programme (EUFORGEN) Secretariats into its new structure, i.e. the new Conservation and Availability of Genetic Resources and Conservation and Use of Forest Genetic Resources programmes. The two networks, ECPGR and EUFORGEN, will consider whether to produce their own newsletter in the future.